An update on best practice in the diagnosis and management of post-prostatectomy anastomotic strictures. (May 2017) - Rocco, Nicholas R; Zuckerman, Jack M
Postprostatectomy vesicourethral anastomotic stenosis (VUAS) remains a challenging problem for both patient and urologist. Improved surgical techniques and perioperative identification and treatment of risk factors has led to a decline over the last several decades. High-level evidence to guide management is lacking, primarily relying on small retrospective studies and expert opinion. Endourologic therapies, including dilation and transurethral incision or resection with or without adjunct injection of scar modulators is considered first-line management. Recalcitrant VUAS requires surgical reconstruction of the vesicourethral anastomosis, and in poor surgical candidates, a chronic indwelling catheter or urinary diversion may be the only option. This review provides an update in the diagnosis and management of postprostatectomy VUAS.